Synthesis and Antibacterial Screening of PolysubstitutedAlkene Derivatives - Gupta, R.N.; Vaidya, V.A.; Bhatia, N.M.; Kokare, C.R.; Singhvi, I.; Bhatia, M.S. (Asian Journal of Chemistry, 2010)
A mini combinatorial library of bi- and tri-substituted alkenes was synthesized and screened for antibacterial activity against Bacillus subtilis, Staphylococcus aureus, Escherichia coli and Pseudomonas aeroginosa. The library of substituted alkenes was obtained by nucleophilic condensation of some carbonyl compounds with a set of active methylene reagents under base catalysis. Screening of the pooled compounds for antibacterial activity and subsequent identification of the lead compound was done by two dimensional deconvolution analysis. The pure lead compound, 1-naphthyl-2-(2-carboxy 3-nitrophenyl) ethene, was synthesized and characterized using TLC, IR, nothing sup 1H NMR and elemental analysis.